A Single‐Step Electrochemical Synthesis of Luminescent WS2 Quantum Dots. Issue 38 (13th June 2017) - Valappil, Manila O.; Anil, Athira; Shaijumon, Manikoth; Pillai, Vijayamohanan K.; Alwarappan, Subbiah
Abstract: Transition‐metal dichalcogenide quantum dots (TMDQDs) with few layers are in the forefront of recent research on tailored 2D layered materials owing to their unique band structure. Such quantum dots (QDs) draw wide interest as potential candidates for components in optoelectronic devices. Although a few attempts towards single step synthesis of MoS2 QDs have been demonstrated, limited methods are available for WS2 QDs. Herein, we demonstrate a one‐step electrochemical synthesis of luminescent WS2 QDs from their bulk material. This is achieved by a synergistic effect of perchlorate intercalation in non‐aqueous electrolyte and the applied electric field. The average size of the WS2 QDs is 3 ±1 nm ( N =102) with few layers. The QDs show a higher photoluminescence (PL) quantum efficiency (5 %) and exhibit an excitation wavelength‐dependent photoluminescence. This unprecedented electrochemical avenue offers a strategy to synthesize size tunable WS2 nanostructures, which have been systematically investigated by various characterization techniques such as transmission electron microscopy (TEM), photoluminescence and UV/Vis spectroscopies, and X‐ray diffraction (XRD). Time‐dependent TEM investigations revealed that time plays a vital role in this electrochemical transformation. This electrochemical transformation provides a facile method to obtain WS2 QDs from their bulk counterpart, which is expected to have a greater impact on the design and development of nanostructures derived from 2D materials. Abstract : Going dotty : Single‐step electrochemical synthesis of WS2 quantum dots at room temperature.